2016
DOI: 10.1182/blood-2015-11-679571
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin mutants in mice induce an MPL-dependent thrombocytosis with frequent progression to myelofibrosis

Abstract: Key Points Calreticulin type I and type II mutants are drivers of the disease as they induce thrombocytosis in a retroviral mouse model. Thrombopoietin receptor MPL is required for calreticulin mutants to induce an essential thrombocythemia phenotype in transplanted mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
260
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(305 citation statements)
references
References 23 publications
34
260
3
1
Order By: Relevance
“…Accordingly, we also found that the myelofibrosis-free survival was longer in CALR type2 patients than all other genotypes. Interestingly, in retroviral model of CALR mutation, mice expressing type1 mutations developed more severe myelofibrosis trait as compared with type2 [29]. On the opposite, an excess of CALR type2 mutations was found in Chinese patients with PMF (64% versus 32% type1) [30] suggesting possible genetic background differences.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, we also found that the myelofibrosis-free survival was longer in CALR type2 patients than all other genotypes. Interestingly, in retroviral model of CALR mutation, mice expressing type1 mutations developed more severe myelofibrosis trait as compared with type2 [29]. On the opposite, an excess of CALR type2 mutations was found in Chinese patients with PMF (64% versus 32% type1) [30] suggesting possible genetic background differences.…”
Section: Discussionmentioning
confidence: 95%
“…43 Differences in cytosolic calcium mobilization have been reported with the 52 base pair deletion, 44 suggesting that this may be one mechanism by which mutant CALR exerts its effect, and expression of the mutant protein does appear to be particularly restricted to megakaryocytes on immunohistochemical evaluation of bone marrow specimens. 45 More recently, it has been shown that CALR mutations can impart TPO-independence in both cell lines 46,47 and retroviral mouse models, 48,49 in a MPL-and JAK2-dependent manner, mimicking the effect of activating MPL mutations. This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…45 More recently, it has been shown that CALR mutations can impart TPO-independence in both cell lines 46,47 and retroviral mouse models, 48,49 in a MPL-and JAK2-dependent manner, mimicking the effect of activating MPL mutations. This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation. 46,49 It is therefore clear that the inappropriate activation of JAK2 signaling is common to the three main phenotypic driver mutations (i.e., those in CALR, MPL and JAK2 itself) and plays an important role in disease pathogenesis in each case, in keeping with the clinical efficacy of JAK2 inhibition irrespective of the presence of the mutations in JAK2.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…1,2 In the last few years, there have been significant advances in our understanding of the genetic basis, pathophysiology, and clinical course of ET. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Our article aims to offer up-to-date information and guidance regarding diagnosis and treatment of ET patients. To provide directions in the therapeutic management of common or complex clinical situations of the disease,…”
Section: Introductionmentioning
confidence: 99%